Crimes and Crime Dispersion in Urban Areas in Turkey - Sargin, Sevil; Temurçin, Kadir (Bulletin of Geography. Socio-economic Series, 2010)
Crime is a phenomenon that arises from the interaction between social, political, economic, physical, psychological circumstances and geographical factors. Since crime occurs in geographical locations, the relationship between crime and location is worth discussing characteristics of a location occur in differents ways. Not only natural geographical factors but also human geographical factors may lead to crime. In this study, the situation, distribution of crimes in the cities which are in the police service zone are dealt with. In addition to crime dispersion in the cities and crimes committed to people and property, crimes committed by month is also studied. In this context, it is seen that since city centres are composed of dense population and urban functions, they feed crime, social control weakens in those areas and they create opportunities for criminals. This causes weakness in society and social capital apart from economic losses in cities. The number of crime incidents, which was 229,513 in 1995, in Turkey, has risen to 785,510 in 2006 with a 3.4 fold increase. 41% of the crimes which were committed in the year of 2006 were against people, 59% were against property.